Exploring the Dynamics of CO2 Emissions, FDI, and Technological Innovation on Economic Growth: Evidence from BRICS Nations by Using CS-ARDL - Noureen, Tyiba; Malik, Muhammad Zahid; Khuhro, Nisar Ahmed; Zafar, Muhammad Ali (Pakistan Journal of Humanities and Social Sciences, 2024)
This research paper aims to determine the relationship between CO2 emissions, FDI, TR, TI, GCF, and LFPR on GDPP in the BRICS region, and finding emphases on the period between 2000-2023. The study further examined the relationship between the dependent and independent variable in the long-run and in the short-run by using the CS-ARDL. The outcomes from CS-ARDL reveal that CO2 emissions, FDI, TI, and GCF affect GDPP significantly. CO2 is, undoubtedly, an adverse phenomenon to the environment but corresponds to the increased level of industrial production and temporary EG. While trade and labor force participation rate have an insignificant relationship with GDP per capita. These findings mean that policy initiatives aimed at technology development, FDI attraction, and encouragement of capital investment should remain priorities in BRICS countries; at the same time, concerns about environmental issues such as CO2 emissions should also be on the agenda for sustainable long-run growth.